Utilization of Information Technology as an Innovation in Islamic Religious Education Learning at Pondok Pesantren Nurul Abshor, Kotabaru - Hilal Solikin; Syaiful Bahari; Arbain Arbain; Ferdi Al Hafizd Ferdi Al Hafizd; Purlinasari Purlinasari; Fina Rosalinda (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to examine information technology-based learning innovations and their impact on the quality of education at the Nurul Abshor Islamic Boarding School in Kotabaru. The study employs a qualitative approach with a descriptive research design. The research subjects consist of Islamic Religious Education teachers, the boarding school leadership, and students. Data collection techniques include observation, interviews, and documentation. Data analysis involves the stages of data reduction, data presentation, and conclusion drawing, while data validity is ensured through source and technique triangulation. The findings indicate that the information technology-based learning innovations at the Nurul Abshor Islamic Boarding School—implemented through the use of instructional videos, projectors, and the internet as learning resources—have proven effective and interactive. The use of instructional videos and projectors has been shown to enhance student focus, motivation, and comprehension through the systematic and engaging visualization of material, while the use of the internet has successfully broadened learning resources and improved students' digital literacy and independence.